PENGARUH EDUKASI MEDIA POSTER TERHADAP PENGETAHUAN MASYARAKAT USIA 19 – 30 TAHUN TENTANG COVID-19 (Jurnal Kesehatan Siliwangi, 2021)
Corona Virus Disease 2019 is an infectious disease caused by the SarsCoV-2 virus. One of the causes of the ongoing increase in the number of Covid-19 cases is the lack of public awareness about the virus in RW 02, Cipadung Kidul Village, Panyileukan District, Bandung City. The purpose of this study was to determine the effect of education through poster media on the knowledge of people aged 19 – 30 years about Covid-19 in RW 02, Cipadung Kidul Subdistric, Panyileukan Distric, Bandung City. This research used a quantitative study design One Group Pretest Posttest Design with a quasi-experimental method. The subjects is 36 respondents from the community aged 19-30 years living in RW 02. The data collection was form of a pretest posttest questionnaire about knowledge of Covid-19. The results of the study found that the significance value was 0.000, which means it is smaller than the p value = <0.05, means Ho is rejected and H1 is accepted. That’s means, there are effect of education through posters on the knowledge of people aged 19-30 years in RW 02, Cipadung Kidul Subdistric, Panyileukan District about Covid-19. The recommendation is the poster can be used as an alternative media to increase public knowledge that can be placed in where information.